PRELIMINARY STUDY OF SCD14 AND SCD163 AS PREDICTORS OF DISEASE SEVERITY AND ICU ADMISSION IN COVID-19: RELATION TO HEMATOLOGICAL PARAMETERS, BLOOD MORPHOLOGICAL CHANGES AND INFLAMMATORY BIOMARKERS - Attia, hend (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Abstract.Background and Objectives: Research supports the role of monocyte/macrophage activation in COVID-19 immunopathology. This study aimed to evaluate sCD14 and sCD163 -the monocyte activation markers -and to investigate their relation to hematological parameters and blood morphology in COVID-19 infection. Methods: This is a case-control study that included 70 COVID-19 patients. Patients were subdivided into two groups: 23 severely diseased ICU-admitted patients and another group of 47 non-ICU-admitted patients. sCD163 and sCD14 levels were determined using ELISA.Results: sCD163 and sCD14 showed significantly higher levels in sera of patients compared to the control group, with significantly higher levels of sCD163 in ICU-admitted patients than non-ICU admitted patients. Receiver operating characteristic curve analysis demonstrated the usefulness of sCD163 with a cut-off value of 734 ng/mL as a potential marker to discriminate between ICU and non-ICU admitted COVID-19 patients (sensitivity of 81.16%; specificity of 96.67% and positive predictive value of 98% with area under the curve of 0.930). sCD163 levels showed a positive correlation with total white blood cells, absolute neutrophilic count, Neutrophil/Lymphocyte ratio, and a negative correlation with platelet count. sCD14 levels positively correlated with D-dimer values associated with a shift to the left and neutrophilic toxic granulations in blood morphology. Conclusion: High sCD163 and sCD14 levels, hematological parameters, and blood morphology reflect monocyte activation in COVID-19 infection. sCD163 is a potential marker of disease severity. These findings support further study of therapeutics targeting macrophage activity in COVID-19 patients with high sCD163 levels.